La place des organismes interétatiques de bassin dans la gouvernance de l’eau partagée - Vanessa Richard (VertigO)
From an Integrated Water Resources Management point of view, international basin organizations should head the governance of shared water resources management. In practice however, when the instruments which institute these organizations make provision for such a role, there is a gap between the texts’ provisions and a much more complex reality. Many international basin organizations fail to play their role of supervisor of water management. Three reasons appear to account for this failure. First, in most cases they are not given the tools which would allow them to build their governance, that is to say they do not have enough a priori and a posteriori control means to ensure the basin States’ implementation of their commitments. Second, when international basin organizations gather emerging or developing countries, the leading role of financing partners in the planning of activities and the functioning of these organizations can result in a decision-making power dispersal or relocation, whether the financing comes from official development assistance or from private investment. Finally, the lack of direct participation of all stakeholders creates discrepancies between needs and activities which are prejudicial to the legitimacy of basin organizations.